ANALISIS PRAKTIK MAKELAR JUAL BELI TANAH PERSPEKTIF HUKUM ISLAM DI DESA MEKARJAYA KECAMATAN GANTAR, KABUPATEN INDRAMAYU, JAWA BARAT - Wahid Nur Salim; Irvan Iswandi (Jurnal Penelitian Multidisiplin Ilmu, 2023)
The rise of buying and selling land that occurred in the village of Mekarjaya assisted by brokers made researchers want to know the actual practice, because many cases occurred regarding land disputes, but for the general public the practice of brokers is considered as a helper in brokering land sales and purchases.This study aims to determine the actual practice of brokers in the community, especially in Mekarjaya Village and to determine the calculation of wages received by brokers in the Islamic Law Perspective.This study uses a qualitative approach specifically more directed at descriptive qualitative research design. Sources of data in this study using primary data sources and secondary data. The data collection technique was carried out by: 1) observation, 2) guided free interviews.Based on the results of the study, the practice of buying and selling land brokers that occurred in the village of Mekarjaya were as follows: 1) The land owner conveyed to the broker/mediator in his closest neighborhood. 2) The broker/mediator checks related documents such as AJB/seller's land certificate. 3) The land owner and the broker make an agreement on the price of the land to be sold and the wages to be received by the broker are generally 2% to 5%. 4) The broker/mediator begins to work by conveying information to his partners and potential buyers. 5) The broker brings together the prospective buyer and the seller to see the condition of the land and make a price agreement. 6) After the transaction is successful/goals, the seller pays the agreed wages to the broker/mediator according to the initial agreement. The practice of buying and selling land brokers in Mekarjara Village is in accordance with the perspective of applicable Islamic law. Because it does not come out of the signs that have been set in Islamic law.